Sri Lanka : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This paper attempts to assess the impact of the oil shock on South Asian economies, including Sri Lanka, as well as policy responses to deal with the shock, and the real income loss for low-income households if fuel subsidies were fully removed. The most important impact has been on the balance of payments followed by the results of poverty and social impact analysis (PSIA) conducted for Sri Lanka. Finally, the paper explores to what extent Sri Lanka's large receipts of worker remittances serve as a hedge against shocks.